2007
DOI: 10.1002/ijc.22521
|View full text |Cite
|
Sign up to set email alerts
|

HPV16‐E6 mRNA is superior to cytokeratin 19 mRNA as a molecular marker for the detection of disseminated tumour cells in sentinel lymph nodes of patients with cervical cancer by quantitative reverse‐transcription PCR

Abstract: About 10-15% of patients with cervical cancer suffer from recurrence despite histologically negative lymph nodes (pN0). Occult micrometastases or small tumour cell clusters may contribute to disease outcome. The aim of this study was to compare at the RNA level 2 known tumour-associated genes, HPV16-E6 and cytokeratin 19 (CK19), as molecular markers for the detection of disseminated tumour cells. Real-time reverse transcription PCR technology was used to quantify gene expression in histologically positive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 42 publications
(41 reference statements)
3
32
1
2
Order By: Relevance
“…It is important to keep in mind, however, that cytokeratin is found in the lymph nodes and blood of healthy individuals [35]. In addition, the technique for detecting cytokeratin is reportedly nonspecific and inferior to HPV-based assays for the detection of metastatic foci in patients with cervical cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to keep in mind, however, that cytokeratin is found in the lymph nodes and blood of healthy individuals [35]. In addition, the technique for detecting cytokeratin is reportedly nonspecific and inferior to HPV-based assays for the detection of metastatic foci in patients with cervical cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…The E6 and E7 genes exert their transforming function by interrupting cell differentiation and inducing DNA synthesis. They accomplish this by interacting with the cellular tumor suppressor gene products p53 and pRB [4] . Zheng et al [5] found that the episomal form of HPV16 was detected in most CIN I, but that the episomal form and the integrated form coexisted in 42.9% of CIN I.…”
Section: Correlation Between Viral Load Of Hpv and Cervical Cancermentioning
confidence: 99%
“…Similarly, TWIST and vimentin are considered as diagnostic markers for hepatocellular carcinoma. Häfner et al [14] have isolated CTCs from metastatic cervical cancer patients and evaluated levels of HPV16-E6 mRNA by real-time PCR, as a more sensitive molecular marker than CK19 mRNA. At the same time, Kuhlmann et al [15] have shown that ERCC1+ CTCs can predict platinum resistance therapy in ovarian cancer.…”
Section: Molecular Profiling Of Ctcsmentioning
confidence: 99%